Clinical usefulness of kidney biopsy in liver transplant recipients with renal impairment - Jong Hoon Lee; Yul Hee Cho; Seung Jee Ryu; Sin Seung Kim; Youn Hee Lee; In-Ae Jang; Bum Soon Choi; Jong Young Choi; Dong Goo Kim; Yeong Jin Choi; Chul Woo Yang; Byung Ha Chung (The Korean Society of Nephrology, 2013)
Background: Chronic kidney disease is a common complication after liver transplantation. In this study, we analyzed the results of kidney biopsy in liver transplantation recipients with renal impairment. Methods: Between 1999 and 2012, 544 liver transplants were performed at our hospital. We retrospectively analyzed the clinical and histological data of 10 liver transplantation recipients referred for kidney biopsy. Results: The biopsies were performed at a median of 24.5 months (range, 3-73 months) after liver transplantation. The serum creatinine level was 1.81±0.5 mg/dL at the time of kidney biopsy. There were no immediate complications. The most common diagnosis was glomerulonephritis (GN), such as immunoglobulin A nephropathy (n=4), mesangial proliferative GN (n=1), focal proliferative GN (n=1), and membranous GN (n=1). Typical calcineurin inhibitor (CNI)-induced nephrotoxicity was detected in three cases (30%). Chronic tissue changes such as glomerulosclerosis, interstitial fibrosis, and tubular atrophy were present in 90%, 80%, and 80% of cases, respectively, and mesangial proliferation was detected in 40% of cases. We began treatment for renal impairment based on the result of kidney biopsy; for example, angiotensin-receptor blockers or steroids were prescribed for GN, and the CNI dose was reduced for CNI nephrotoxicity. As a result, eight of 10 patients showed improvement in glomerular filtration rate, but two progressed to end-stage renal disease. Conclusion: Kidney biopsy is a safe and effective method for determining the cause of renal impairment after liver transplantation. Management of patients based on the result of kidney biopsy may improve renal outcomes.